RESPECT FOR THE PROPHET'S FAMILY AND HIS DESCENDANTS IN THE TAFSIR OF AL-MISBAH - Pramudiya Citra Sholeha Hindratma (Tahiro : Journal of Peace and Religious Mederation, 2025)
This research was motivated by the researcher's great curiosity about the Muslim community's respect for Ahl Al Ba?t or descendants of the Prophet Muhammad SAW. Apart from that, researchers also want to study the glory of Ahl Al-Ba?t contained in the Koran. The focus studied in this research is who is included in Ahl Al-Ba?t and how is Quraish Shihab's perspective in Tafsir Al-Misbah related to Ahl Al-Ba?t. This study using the Library Research approach or literature research and the data sources used are the Book of Tafsir AL-Misbah and relevant literature and informants from the descendants of the Prophet Muhammad SAW in Indonesia. The data collection methods used are interviews and documentation. The data analysis techniques used are data reduction techniques, data presentation and drawing conclusions/data verification. While to check the validity of the data the researcher uses source triangulation, method triangulation, and time triangulation. Based on the research results, it can be concluded that those included in the ahl al-Ba?t are the descendants of Rasulullah SAW, his wives, and all Muslims and Muslim women from the descendants of 'Abdul Muththalib, namely Bani Hayim. Therefore, Ahl Al-Ba?t includes the families of Ali bin Abi Thalib, Hasan and Husein, the Ja'far family'far bin Abi Thalib, family'Aqil bin Abi Thalib, and family'Abbas bin 'Abdul Muttalib. Homage to Ahl Al-Ba?t is an obligation for Muslims to do because of respect for Ahl Al-Ba?t is the same as respecting the Prophet Muhammad SAW, even more so respecting Ahl Al-Ba?t, of course, as someone who claims to be a follower of the Prophet, it is appropriate and fitting to respect the Prophet, which includes respecting the Prophet is respecting his family and all his dzuriyyah. A form of respect for Ahl Al-Ba?t by glorifying them, trying to help them with their affairs when needed, loving their hearts and their words